2002
DOI: 10.1037/0022-3514.82.5.722
|View full text |Cite
|
Sign up to set email alerts
|

Thought confidence as a determinant of persuasion: The self-validation hypothesis.

Abstract: Previous research in the domain of attitude change has described 2 primary dimensions of thinking that impact persuasion processes and outcomes: the extent (amount) of thinking and the direction (valence) of issue-relevant thought. The authors examined the possibility that another, more meta-cognitive aspect of thinking is also important-the degree of confidence people have in their own thoughts. Four studies test the notion that thought confidence affects the extent of persuasion. When positive thoughts domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
447
6
17

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 444 publications
(509 citation statements)
references
References 80 publications
26
447
6
17
Order By: Relevance
“…More concretely, participants were exposed to a computer outcome and were told either that "you are strongly associated with vegetables" or that "you are strongly associated with animals." This kind of manipulation based on a false self-concept feedback has worked successfully in the past to influence people's beliefs about themselves Petty, Briñol, & Tormala, 2002). Research using implicit measures has also revealed that changes in categorization can influence automatic responses relevant to the self (see Gawronski & Sritharan, 2010 for a review).…”
Section: Independent Variables False Feedback (Implicit Self-vegetabmentioning
confidence: 99%
“…More concretely, participants were exposed to a computer outcome and were told either that "you are strongly associated with vegetables" or that "you are strongly associated with animals." This kind of manipulation based on a false self-concept feedback has worked successfully in the past to influence people's beliefs about themselves Petty, Briñol, & Tormala, 2002). Research using implicit measures has also revealed that changes in categorization can influence automatic responses relevant to the self (see Gawronski & Sritharan, 2010 for a review).…”
Section: Independent Variables False Feedback (Implicit Self-vegetabmentioning
confidence: 99%
“…Drawing on the self-validation hypothesis (Petty et al, 2002; for a review, see Briñol & Petty, 2009), participants who read the pro-social neighbor message generated positive thoughts toward the target and those who read the anti-social neighbor message generated negative thoughts toward the target (with the possibility of generating thoughts about punishment). Then, the ethics or legality prime played a self-validating role, leading participants to rely more on their thoughts in these conditions than in the control condition.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on the self-validation hypothesis in persuasion (Petty, Briñol, & Tormala, 2002; for a review, see Briñol & Petty, 2009), people's reliance on and use of their social judgments can vary as a function of other variables. We hypothesize that one of these variables that might increase people's reliance on their judgments (and therefore, their use) may be justice accessibility.…”
Section: Self-validation and Justice Accesibilitymentioning
confidence: 99%
“…o "confío en mis pensamientos acerca de la bondad de este producto" (Jost, Kruglanski & Nelson, 1998). En este caso, una variable persuasiva ya no afectará las actitudes a través de un proceso relacionado a la generación de pensamientos, sino a uno vinculado a la metacognición, como, por ejemplo, la validez que se le otorgan a los propios pensamientos (Petty, Briñol & Tormala, 2002). Ejemplos de variables que pueden actuar a través de uno u otro proceso, dependiendo del momento de presentación, son el rol que posee el poder del receptor (de entregar recompensas y castigos; Briñol, Petty, Valle, Rucker & Becerra, 2007), el rol de la afirmación de la identidad del receptor (Briñol, Petty, Gallardo & DeMarree, 2007), el rol de la credibilidad que posee la fuente de información (Tormala, Briñol & Petty, 2006), el rol de la mayoría o minoría numérica (Horcajo, Petty & Briñol, 2010), entre otros.…”
Section: Algunas Limitaciones En El Estudio De Las Prs En Psicología unclassified